“The Teacher Himself Feels Shy, So How can We Ask Questions to Him?”: Classroom Ecosystem of Comprehensive Sexuality Education in the Schools of Nepal - Pokharel, Sharmila; Devkota, Bhimsen; Bhandari, Sabindra Raj (NPRC Journal of Multidisciplinary Research, 2025)
Comprehensive Sexuality education is still taboo in a developing country like Nepal. Although many studies around the world have demonstrated the effectiveness of well-implemented school-based CSE in promoting sexual and reproductive health outcomes for young people, studies from Nepal show that the prevalence of teenage pregnancy among school-going adolescents has failed to meet the objectives of reducing students’ risk, enhancing decision-making capacity, and enhancing self-efficacy. Therefore, this study focused on students’ experiences of school-based CSE in Nepal. This study was qualitative. Data were collected from 68 participants across four schools in the study setting using focus group interviews. An explanatory phenomenological analysis framework was followed to analyze the data. Students feel hesitant to discuss at home regarding sexual matters. Peers and the internet were found to be the most popular sources of learning. Students want open and frank communication, a flexible learning environment, and an inclusive school environment. A diverse teaching approach is needed for it. Using a peer teaching approach, as well as ongoing in-service, pre-service, active participatory training and retraining interventions, and support for sex education teachers, to address the identified barriers and improve their pedagogical effectiveness.